Teaching of the subject "Energy frombiomass" in the Renewable Energies European Master: the Bera group experience - Maryori Díaz; Daniel García; Maider Gómez; Eva López; Daniel Maraver; Adeline Rezeau; Fernando Sebastián (Universidad de La Rioja, 2013)
In order to reinforce and develop the skills of the postgraduate students in the so-called "Energy from Biomass" subject within the European Masters in Renewable Energies, the BERA Group (Biomass, Evaluation, Resources and Use) of the CIRCE Research Institute (Centre for the Research of Energy Resources and Consumptions) carries out a series of practical sessions oriented to motivate and orientate the student in the execution of group work and presentations in a limited period of time. In this manner, the students must face similar situations to the ones that they would confront during the carrying out of real projects in the field of Renewable Energies in a business and/or research environment. The different teaching sessions analyzed in the present paper are oriented to achieve a main objective which is to consolidate the acquired knowledge in the theoretical sessions, as well as attaining a not less important objective: joining different disciplines of Engineering and Economy, which is very advisable due to the diversity of the students in the Master. This paper presents the basis for the session preparation, their desired objectives and the conclusions obtained by the teaching staff after their implementation.